Variant rs6596140 of Follistain-like 4 gene (FTSL4) may be associated with poor response to angiotensin receptor blockers (ARBs) among Filipinos - Ona, Deborah Ignacia D.; Nevado, Jose B. Jr; Ramos, John Daniel A.; Llanes, Elmer Jasper B.; Magno, Jose Donato A.; Punzalan, Felix Eduardo R.; Reganit, Paul Ferdinand M.; Santos, Lourdes Ella G.; Tiongco, Richard Henry II P.; Aherrera, Jaime Alfonso M.; Abrahan, Lauro L. IV; Agustin, Charlene F.; et al. (Vol.150, No.4 (August 2021) pages 703-710.)
"Constituting one of the most commonly used antihypertensive drug families are the angiotensin receptor blockers (ARBs). The aim of this study was to identify the variants associated with response to ARBs that may potentially be used as markers for designing a tailor-fit treatment strategy for hypertension. An unmatched case-control study was done among adult hypertensive Filipino patients maintained on ARBs. Genotypic analysis of blood DNA was conducted"-Title page.